Effects of Endotracheal Extubation with Suctioning versus Positive Pressure in Children after General Anaesthesia, A clinical Trial - Khan, Kenan Anwar; Mahmood, Tariq; Yasin, Bilal; Muhammad Zeeshan Akbar; Shaista Mumtaz; Fahim Liaqat (Pakistan Armed Forces Medical Journal, 2023)
Objective: To observe the effects of extubation with suctioning when compared with extubation with positive pressure in children after general anaesthesia. Study Design: Randomized Control Trial (ClinicalTrials.gov: NCT05489809). Place and Duration of Study: Main Operation Theatre (OT), PNS Shifa Hospital, Karachi Pakistan, from Mar to Aug 2022. Methodology: Patients were randomly divided into two groups of 40 patients each. One group of patients was extubated after general anaesthesia with negative pressure/suctioning applied to the ETT. In contrast, the other group of patients was extubated by applying positive pressure to the ETT. The need for additional suctioning more than once and supplemental oxygen, if required, was documented in the first 3 minutes after extubation (primary endpoints). Additionally, hemodynamic and respiratory parameters were documented at the time of extubation and 3 minutes after (secondary endpoints). Results: The results showed that 12(30%) patients out of 40 in the Negative Pressure Extubation-Group required additional suctioning within the first 3 minutes after extubation compared to only 3(7.5%) patients in the Positive Pressure ExtubationGroup. Furthermore, 3(7.5%) patients in the Negative Pressure Extubation-Group required supplemental oxygen 3 minutes after extubation compared to only 1(2.5%) in the Positive Pressure Extubation-Group. Conclusion: We observed that negative pressure extubation, when compared to positive pressure extubation, increased the requirement for suctioning and supplemental oxygen in the first 3 minutes after extubation.